External Financing Risks : How Important is the Composition of the International Investment Position? - Cubeddu, Luis.; Hannan, Swarnali; Rabanal, Pau. (Washington, D.C. : International Monetary Fund, 2021)
Building on the vast literature, this paper focuses on the role of the structure of the international investment position (IIP) in affecting countries' external vulnerabilities. Using a sample of 73 advanced and emerging economies and new database on the IIP's currency composition, we find that the size and structure of external liabilities and assets, especially with regards to currency denomination, matter in understanding balance-of-payments pressures. Specifically, and beyond the standard macroeconomic factors highlighted in other studies, higher levels of gross external debt increase the likelihood of an external crisis, while higher levels of foreign-currency-denominated external debt increase the likelihood of sudden stops. Foreign reserve assets play a mitigating role, although with diminishing returns, and the combination of flow and stock imbalances amplifies external risks, especially during periods of heightened global risk aversion. The results are especially strong for emerging economies, where the impact of flow and stock imbalances and foreign currency mismatches are larger and more robust across specifications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet